Upaya dalam Meningkatkan Literasi dan Numerasi terhadap Siswa Jenjang Sekolah Dasar di Kelas 6 - Dewi Nirwana Ayu Kirani; Filia Dwi Lestari; Astri Widyaruli Anggraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
The author conducted this research based on the low literacy and numeracy abilities of students. This research activity was attended by grade 6 students, where this activity aims to be able to improve literacy and numeracy skills for students. In this study, the author used a qualitative research method by observing the actions of a person directly and then describing them in detail so that readers could understand them. This research activity has three stages, namely the first stage is planning an activity to be carried out, the second stage is the implementation process to observe grade 6 students, and the third stage is the evaluation and conclusion stage. Based on the research results, it was found that students will tend to have literacy skills if they continue to practice literacy and learn numeracy. In addition, if the learning process is carried out by learning while playing so that these students can develop a strong sense of enthusiasm in learning literacy and numeracy.